In vivo X-ray digital subtraction and CT angiography of the murine cerebrovasculature using an intra-arterial route of contrast injection - Negrão de Figueiredo Miller, Giovanna; Boll, Hanne; Groden, Christoph; Brockmann, Marc Alexander (American journal of neuroradiology, 2012)
BACKGROUND AND PURPOSE: Investigation of the anatomy, patency, and blood flow of arterial and venous vessels in small animal models of cerebral ischemia, venous thrombosis, or vasospasm is of major interest. However, due to their small caliber, in vivo examination of these vessels is technically challenging. Using micro-CT, we compared the feasibility of in vivo DSA and CTA of the murine cerebrovasculature using an intra-arterial route of contrast administration. MATERIALS AND METHODS: The ECA was catheterized in 5 C57BL/6J mice. During intra-arterial injection of an iodized contrast agent (30 μL/1 sec), DSA of the intra- and extracranial vessels was performed in mice breathing room air and repeated in hypoxic/hypercapnic mice. Micro-CTA was performed within 20 seconds of intra-arterial contrast injection (220 μL/20 sec). Image quality of both methods was compared. Radiation dose measurements were performed with thermoluminescence dosimeters. RESULTS: Both methods provided high-resolution images of the murine cerebrovasculature, with the smallest identifiable vessel calibers of ≤50 μm. Due to its high temporal resolution of 30 fps, DSA allowed identification of anastomoses between the ICA and ECA by detection of retrograde flow within the superficial temporal artery. Micro-CTA during intra-arterial contrast injection resulted in a reduced injection volume and a higher contrast-to-noise ratio (19.0 ± 1.0) compared with DSA (10.0 ± 1.8) or micro-CTA when using an intravenous injection route (1.3 ± 0.4). CONCLUSIONS: DSA of the murine cerebrovasculature is feasible using micro-CT and allows precise and repeated measurements of the vessel caliber, and changes of the vessel caliber, while providing relevant information on blood flow in vivo.